Upaya Karyawan BSI KCP Gunung Tua dalam Menghadapi Pra Pensiun - Bako, Risma Wati; Tambunan, Khairina (Medan Resource Center, 2022)
Work is a human effort to fulfill the needs of daily life. In work, humans usually use the skills they have according to their respective abilities. The motive of humans to work is not only to fulfill their daily needs, but by working humans can channel their skills. Usually the success of humans as real beings and having intelligence compared to other God's creatures is to have a job, by having a job humans can find out how far humans are in exploring their potential, giving birth to creativity and achieving their goals in humans. life. But gradually humans will enter a period where they decide to retire and quit their jobs. At that time a person's productivity will definitely decrease and experience many changes in the way of thinking and deciding things. In the elderly, usually someone prefers a static job than a challenging job, because it is related to the person's physical condition and ability to do the job. Attitudes generated by a person when they are about to face retirement are different and this can cause problems within themselves or with the surrounding environment. Preparing for retirement can also be done by someone by changing their perspective. Changing one's perspective has wonders and has a huge impact on one's way of thinking, emotions, motivation and mental energy. reality is not changed, but the perspective is changed, so that a person finds a new meaning or understanding of a situation. The analytical method used by the author is a qualitative method. The purpose of this research is to find out how the employees of BSI KCP Gunung Tua face retirement.